1998
DOI: 10.1111/j.1469-8749.1998.tb15445.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep dysfunction in Rett syndrome: a trial of exogenous melatonin treatment

Abstract: Nine girls with Rett syndrome (mean age, 10.1 years) were monitored 24 hours a day over a period of 10 weeks using wrist actigraphy. Baseline sleepwake patterns were assessed for 1 week. Subsequently, patients underwent a 4-week melatonin treatment period in a double-blind, placebocontrolled, crdssover protocol that employed a 1-week washout between treatment trials. Melatonin doses ranged from 2.5 to 7.5 mg, based upon individual body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 34 publications
5
123
2
Order By: Relevance
“…A possible explanation for this is that their study used a standard dose of 5 mg slow-release melatonin, whereas the final doses in our study ranged from 2 to 10 mg (M = 7 mg). This maximum is greater than that used in most other studies of children with neurodevelopmental disorders (range = 1-6 mg: Camfield et al 1996, Dodge andWilson 2001;Andersen et al 2008, 7.5 mg McArthur andBudden 1998). This suggests that some children may require larger doses than those being suggested in the literature, and that there may be considerable variability in dose needed.…”
Section: Primary Outcomesmentioning
confidence: 64%
See 1 more Smart Citation
“…A possible explanation for this is that their study used a standard dose of 5 mg slow-release melatonin, whereas the final doses in our study ranged from 2 to 10 mg (M = 7 mg). This maximum is greater than that used in most other studies of children with neurodevelopmental disorders (range = 1-6 mg: Camfield et al 1996, Dodge andWilson 2001;Andersen et al 2008, 7.5 mg McArthur andBudden 1998). This suggests that some children may require larger doses than those being suggested in the literature, and that there may be considerable variability in dose needed.…”
Section: Primary Outcomesmentioning
confidence: 64%
“…All but two participants improved on sleep latency (time to onset of sleep), but there were no differences in the number of wakenings. In another double blind study, sleep latency also improved significantly in a group of nine children with Rett syndrome following 1 month of melatonin (McArthur and Budden 1998). The third trial, which did not report sleep improvements with melatonin, only included six participants (Camfield et al1996).…”
Section: Introductionmentioning
confidence: 95%
“…166 In one small clinical trial (n=9) melatonin appeared to improve total sleep time and efficiency in those worse at baseline without any adverse side effects. 170 Given the frequency and impacts of sleep dysfunction on child and family, our evidence base for management remains remarkably sparse.…”
Section: Sleep Disturbancesmentioning
confidence: 99%
“…Other trials have tested the effects of melatonin for nocturnal sleep disturbance in children with a range of neurodevelopmental difficulties. [154][155][156] Many of the children included in these studies had at least one comorbid disability (e.g., epilepsy, blindness), and all had disturbed sleep-wake patterns. Although considerable inter-individual variability was observed in the response to melatonin, all of the studies showed significant improvements in at least one sleep measure.…”
Section: Melatonin In Children/adolescents With Iswrd and Neurologic mentioning
confidence: 99%
“…Melatonin was recommended at the OPTION level in the previous Practice Parameters for children with various neurologic disorders, 1 based upon four studies, [153][154][155][156] none of which was eligible for the current review, due to an insufficient number of participants or grouping of participants with different CRSWDs. One new eligible study was identified, 157 and melatonin was shown to improve select predefined CRITICAL outcomes (TST, ISL), although the confidence interval associated with both values crossed the threshold of the predetermined clinically significant minimal change (see Table 2).…”
Section: Melatonin In Children/adolescents With Iswrd and Neurologic mentioning
confidence: 99%